Pengaruh Gaya Kepemimpinan dan Ketrampilan Kerja Tim di Kapal Terhadap Keselamatan Pelayaran Menurut Undang -Undang Pelayaran - S. Teguh Wiyono; Kuncowati Kuncowati (Majalah Ilmiah Bahari Jogja, 2020)
When working on commercial vessel and passage ship,crew members get task devided into work teams such as maneuvering, anchoring, navigation,loading,unloading, maintenance, emergency trainning and emergency situations. In working skills are very necessary but sometimes found on board,orders from superior to subordinate are poorly understood,team skill and cohesiveness are lacking.In team cooperation on the ship the leadaership factor and teamwork skills are needed so that the work becomes fast,precise and achieved the objectives of shipping safety,therefore this study aims to analize the influence of leadership and teamwork skills on shipping safety according the RI law ( UU.No.17 Th.2008 ).The sample in this study is a commercial ship crew is at the port of Tanjung Perak Surabaya with a total of 90 ( ninety ) respondent.The method used in this study is the quantity method with linear regression analisys method.The result of this study ara that the leadership factor and team work skills have a positif and significant 44,4% and equation Y = 3,636 + 0,464 X1 +0,331 X2 + µ.